2020
DOI: 10.1371/journal.pone.0236992
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type I collagen in response to Isoniazid exposure is indirect and is facilitated by collateral induction of cytochrome P450 2E1: An in-vitro study

Abstract: We wanted to investigate whether Isoniazid (INH) can directly stimulate activation of hepatic stellate cells (HSCs) and enhance production of collagen. Treatment of human hepatic stellate cell line LX2 with or without 5μM INH for 24 to 72 hours was performed to look into content of cytochrome P450 2E1 (CYP2E1), activity of NADPH oxidase (NOX) and intracellular oxidative stress. Protein level as well as mRNA expression of alpha smooth muscle actin (α-SMA) and collagen1A1 (COL1A1) were assessed by western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…CYP2E1 is an inducible gene that is upregulated under multiple conditions, such as fasting and nutrition intake, as well as in a wide variety of pathophysiological states (2,(12)(13)(14)(15)(16)(17). In addition to metabolizing endogenous substrates and xenobiotics, CYP2E1 is the main source of cellular ROS, and its NADPH oxidase activity is higher than that of other CYP family members (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2E1 is an inducible gene that is upregulated under multiple conditions, such as fasting and nutrition intake, as well as in a wide variety of pathophysiological states (2,(12)(13)(14)(15)(16)(17). In addition to metabolizing endogenous substrates and xenobiotics, CYP2E1 is the main source of cellular ROS, and its NADPH oxidase activity is higher than that of other CYP family members (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can catalyze the reaction of NADPH and O 2 to generate reactive oxygen species (ROS) (7,8). CYP2E1 is the major enzyme for the production of cellular and mitochondrial ROS and reactive nitrogen species (RNS), which induce tissue damage mainly by damaging cellular and mitochondrial macromolecules, including mitochondrial DNA (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the finding was consistent with a previous study from India showing that a diagnostic ATT to distinguish CD from intestinal TB was associated with a higher risk of disease progression ( 8 ). It is assumed that ATT predisposing disease progression may be ascribed to the activation and proliferation of intestinal stromal cells (e.g., fibroblasts, myofibroblasts, and smooth muscle cells) or immune cells, followed by the overproduction of extracellular matrix and profibrogenic cytokines (e.g., transforming growth factor-β, interleukin-17A, and interleukin-6) ( 9 , 10 ). However, the exact mechanism of antitubercular agent-induced intestinal fibrosis needs to be elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has raised a concern over patients with CD who had a history of empirical ATT before CD diagnosis because they were more apt to develop intestinal stricture ( 8 ). Indeed, several studies have demonstrated that ATT agents, including INH and RFP, have the potential to facilitate fibrosis ( 9 , 10 ). Noteworthily, once intestinal fibrosis and its associated complications such as stricture or penetration occur, there are no specific antifibrotic drugs that can reverse the disease progression yet.…”
Section: Introductionmentioning
confidence: 99%
“…INH administered via oral, intramuscular, and intravenous formulations inhibit cytochrome oxidase P450 enzymes and monoamine oxidase [ 141 ]. A critical interaction during TB treatment is its combination with RIF, which can lead to hepatotoxicity [ 142 ].…”
Section: Limitations Of Conventional Therapies In Tb Treatmentmentioning
confidence: 99%